Clinical and economic burden of herpes zoster and postherpetic neuralgia in patients from the National Skin Centre, Singapore - Qiping Chen; Tun-Ying Hsu; Roy Chan; Kosuke Kawai; Camilo J. Acosta; Anuj Walia; Jiun Yit Pan (Wolters Kluwer Medknow Publications, 2015)
Background/Objectives: There is a scarcity of recent data on the burden of herpes zoster (HZ) and postherpetic neuralgia (PHN) in Southeast Asia. We evaluated the prevalence, demographics, and disease burden of HZ and PHN in patients aged ≥ 50 years seen at a tertiary dermatological referral center, the National Skin Centre (NSC), Singapore. Methods: We carried out a retrospective cohort analysis of NSC patient electronic medical records spanning >3 years from January 2010 to March 2013. Data on patient demographics, clinical characteristics, and medical management were collected. Results: A total of 347 cases of HZ or PHN were included in this study. The mean age was 66.5 years with equal proportions of men and women. The majority of patients (85.6%) were of Chinese ethnicity. Patients presented to the NSC at various disease stages including acute HZ (83.0%), subacute HZ (10.7%), or PHN (6.3%). The most commonly affected anatomic site was thoracic dermatome (41.2%) and the most common prodromal symptom was pain (81.8%). In addition, pain was present in various stages of HZ, and it was the most unbearable symptom experienced during illness (85.5%). Patients in the older age group were more likely to suffer from pain for ≥6 months than patients in the younger age group. Most of the patients received antiviral treatment including acyclovir (70.9%) and valaciclovir (13.5%). Among all the patients, 85.0% received analgesia with the most common drugs being amitriptyline (25.4%) and gabapentin (21.9%). PHN led to significantly higher economic burden with a total cost of 414.69 Singapore dollars per patient versus 267.26 Singapore dollars for a non-PHN patient. Conclusion: HZ and PHN cause a significant clinical and economic burden in Singapore.